ANALISIS PERBEDAAN VARIABEL PENENTU KINERJA BIDAN DALAM MENGELOLA DESA/KELURAHAN SIAGA AKTIF BERSTRATA PURI DAN NON PURI DI KABUPATEN LUMAJANG TAHUN 2018 - Vitasari, Ratna; Herawati, Yennike Tri; Ririanty, Mury (Jurnal Ilmu Kesehatan Masyarakat, 2019)
In Lumajang Regency, the coverage of Desa dan Kelurahan Siaga Aktif Puri in 2018 around 15% out 70% target set. The active performance of midwives in development of Desa dan Kelurahan Siaga Aktif is highly expected. They have a role in managing Desa dan Kelurahan Siaga Aktif. This study was a quantitative study aimed to analysis differences of midwives job performance managing desa/kelurahan siaga aktif with puri strata and Non pur strata in Lumajang Regency 2018. The results showed there was significantly different between Desa and Kelurahan Siaga Aktif with Puri Strata and non Puri in Lumajang Regenc among facilities and infrastructure (p = 0,000), training (p = 0.004) and community support (p = 0,000) There was no difference between knowledge variables (p = 0.107), years of service (p = 0.483), domicile (p = 0.546), intrinsic motivation (p = 0.756), extrinsic motivation (p = 0.151), supervision (p = 0.660), midwife performance (p = 0.105) with strata of Desa dan Kelurahan Siaga Aktif Puri with non Puri in Lumajang Regency.It can be concluded midwives among Desa dan Kelurahan Siaga Aktif strata Puri have different facilities and infrastructure, training, community support from the midwives Desa and Kelurahan Siaga Aktif strata non Puri.